Iowa fall bird report, 1994, Babs & Loren Padelford - Padelford, Babset al; Padelford, Lorenet al (1994)
An annotated list of birds sighted by Babs and Loren Padelford. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1994. Plustek - flatbed